ASSESSMENT OF SELECTED COMMERCIAL BROILER CHICKEN DIETS SOLD IN, NIGERIA - Usman, Y.; Muhammed, S.Z.; Gamawa, A. A.; Chongmobmi, M.; Nuhu, Y.; Muhammad, S.; Sabo. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was carried out to assess the utilization of some commercial broiler chicken diets, eight-week study was conducted using two hundred and fifty-five (255) day-old chicks randomly allotted to five diets each treatment diet was replicated three times and each replicate containineds17 birds each in a Completely Randomized Design. Feed and water were served ad libitum. Performance results showed that most parameters (daily feed intake daily weigh gain and feed conversion ratio), at both starter and finisher phases were significantly (P<0.05) influenced by the diets. Overall performance revealed that broiler chickens fed diet 3 had higher (P<0.05) final weight (2530.56 g), followed by those on diet 1 (2293.36 g). Diets 2 (2293.36 g), 4 (2249.99 g) and 5 (2117.74 g) were similar and had lowest value. There was no significant influence (P<0.05) of diet on carcass characteristics, however, some organ parameters differed significantly (P<0.05) among treatments. Respective values of feed cost per kg and feed cost per kg gain were lower on diet 1 (N274.00; N675.78) and higher on diet 5 (N300.00; N774.15). It was concluded that diet 3 gave better performance in terms of final weight and total weight gain and is recommended for broiler chicken farmers.